It's about "time": Why time deficits matter for poverty - Rania Antonopoulos; Thomas Masterson; Ajit Zacharias (Levy Economics Institute of Bard College, 2012)
We cannot adequately assess how much or how little progress we have made in addressing the condition of the most vulnerable in our societies, or provide accurate guidance to policymakers intent on improving each individual's and household's ability to reach a basic standard of living, if we do not have a reliable means of measuring who is being left behind. With the support of the United Nations Development Programme and the International Labour Organization, Senior Scholars Rania Antonopoulos and Ajit Zacharias and Research Scholar Thomas Masterson have constructed an alternative measure of poverty that, when applied to the cases of Argentina, Chile, and Mexico, reveals significant blind spots in the official numbers.
Keywords: 330